Safety and efficacy of peroral endoscopic myotomy with endoscopic fundoplication compared with POEM alone: International multicenter cohort study - Kahaleh, Michel; Hapshy, Vera; Alcívar, Juan A; Baquerizo-Burgos, Jorge; Lukashok, Hannah; Gaidhane, Monica R; Andalib, Iman; Tyberg, Amy; Sarkar, Avik; Shahid, Haroon; Allehibi, Abid; Alkhiari, Resheed; Rodriguez, Magda L; Bautista-Altamirano, Carmen; Rodriguez, Sarbelio; Porfilio, Maria G; Carames, Mine; Carames, Juan Carlos; Bapaye, Amol; Robles-Medranda, Carlos (Endoscopy International Open, 2025)
Gastroesophageal reflux (GERD) can occur in a significant number of achalasia patients undergoing post-peroral endoscopic myotomy (POEM). POEM with endoscopic fundoplication (POEM-F) is a new endoscopic technique to treat post- POEM GERD. We conducted a multicenter cohort study to compare outcomes between POEM and POEM-F.We included patients who underwent POEM or POEM-F from six tertiary centers. Primary outcomes were: 1) clinical success, defined as post-procedure cessation or reduction of proton-pump inhibitors; 2) post procedure percent time pH < 4 and DeMeester score; and 3) post-procedure Eckardt scores. Secondary outcomes included adverse events, procedure time, and hospital stay duration.Sixty-four patients were included: 31 patients underwent POEM-F (mean age 51, 48% male), whereas 33 patients POEM (mean age 56, 58% male). Technical success was 100% in both groups. POEM-F patients achieved reduction/cessation in proton pump inhibitor use in 25 of 31 patients (80%); POEM patients in eight of 33 (24%) (P ≤ 0.00001). Percent time with pH < 4 was significantly lower in the POEM-F group (2.75 +/- 2.53 vs 9.3 +/- 3.6 min, P ≤ 0.0001). Post-procedure DeMeester scores were lower (< 14.7) in POEM-F (mean 9.6) than POEM (mean 15.8) (P ≤ 0.0011). There were three mucosal injuries in the POEM-F group and four in the POEM group. Hospital stay duration and procedure time did not differ between groups. In the POEM group, four patients required Dor fundoplication. No repeat interventions were recommended for the POEM- F group at 6-month follow-up.POEM-F achieves statistically significant improvement in post- POEM GERD compared with POEM alone.
Keywords: Endoscopy Upper GI Tract; Motility / achalasia; POEM